Effect of Different Mordants on Cotton Cloth Dyed with Aspergillus and Penicillium Dyes - Suciatmih Suciatmih; Iman Hidayat (Graduate Program of Syiah Kuala University, 2017)
Natural dyes are an important alternative to potentially harmful synthetic dyes. This research was conducted using three kinds of Aspergillus dyes and six kinds of Penicillium dyes. In this study, Aspergillus and Penicillium were grown in mineral salts glucose medium. Premordanting technique was followed using different mordants, namely alum, CaCO3, CuSO4 5H2O, FeSO4 7H2O, K2Cr2O7 and MnSO4 H2O on cotton cloth. The colour of filtrate and range of colours developed on dyed materials were measured by RHS colour chart. The results indicated that the colour of dyed cloth was influenced by the addition of mordants, andÂ different shades were obtained from the same dye filtrate using different mordants. FeSO4 7H2O was found as the most influential mordant. The present study shows a new source of fungal dyes, which can be used as an alternative for dyeing cloth.